Reading movement in community: A study of Gerakan Buru Membaca - Muhamad Chairul Basrun Umanailo; Aulia Nursyifa (International Journal of Evaluation and Research in Education (IJERE), 2022)
The Buru Reading Movement (Gerakan Buru Membaca) was an initiative of Iqra Buru University community service and developed later into one of the Buru District Government programs, which have been implemented since 2017. The program was designed to improve and promote the community’s reading habits in Buru Regency, Maluku, Indonesia. This was a qualitative study aimed at describing the implementation of Gerakan Buru Membaca in Buru Regency. The research located in Namlea District because of its relatively high population density and heterogeneity. There were forty people interviewed, and this number was obtained through purposive sampling. We employed an analysis technique proposed by Miles and Huberman. The results revealed that the reading movement received a positive response from the community and the village government. The active role is implemented through the provision of village libraries, study rooms, and study houses of learning available. Furthermore, a mobile library, which was only available in the Namlea Village area, prioritized its services in open or public spaces. In other villages, however, the movement was still in the form of reading and learning spaces provided by the village government, with the participation of the community. Despite the positive response from the community, the movement still experienced several constraints.